The Decauville portable railways and the modernization of the Mexican hacienda: The case of production and transportation of henequen and pulque, c. 1880-1907 (Historia Agraria de América Latina, 2022)
This article examines the introduction of the French Decauville portable railway as part of the technological modernization of Mexican haciendas specialized on pulque and henequen. Previous research, focusing on production trends, has not paid attention to this technology that derived from a local innovation in the railroad system, and whose simplicity and affordability were determinant for its adoption in the agricultural sector. The main question we pose is the following: What features of this technology did contribute to haciendas’ specialization on pulque and henequen? In response, we argue that the creative local appropriation and adaptation of this transportation technology added significant advantages to the production-commercialization chain in both crops. The Decauville railway reduced costs and made it possible faster transportation to the market. This research is based on information from a variety of sources, such as government documents, newspapers, statistical yearbooks, bulletins, and Decauville catalogs.
Keywords: Decauville portable railways; Mexican hacienda; technology; agricultural transportation